Senior High Students’ Examination Anxiety and Its Implications for Counselling - Ahenakwa, Simon; Kuranchie, Alfred; Mensah, Monica Konnie (Advances in Social Sciences Research Journal, 2025)
In the contemporary world, students’ future is dependent on their achievement in examination but both empirical and anecdotal evidences evince and attest to the fact that students demonstrate anxiety for examination, be it standardised or non-standardised, internal or external. Yet, not much attention has been paid to some essential aspects of examination anxiety aimed at understanding them in order to help students deal with the phenomenon. This study, therefore, aimed to investigate students’ level of anxiety for examination, the stages of examination where students demonstrate high levels of anxiety as well as the psychophysiological responses to examination anxiety. The cross-sectional study was conducted among senior high school students in the Bono East Region of Ghana. A self-developed questionnaire composing of four sections, which covered the variables of the study was used to gather the research data. Mean, standard deviation and One-way Analysis of Variance were used to analyse the data generated. The study revealed that students demonstrate high level of anxiety during examinations. Besides, the students demonstrate high level of anxiety before and after examination but moderate level of anxiety during examination. The study also disclosed that the students exhibit varying psychophysiological responses to anxiety before, during and after examination. The study, therefore, recommends for psychological counselling to equip high school students with the competence to overcome anxiety at all stages of examination to trigger enviable performance to enhance their fortune and wellbeing.